Issues and Aspects of Comparative Long-term Studies in Youth Unemployment in Europe: Biographical Constructions of “Generation Y” - Ernst, Stefanie (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
Youth unemployment is still a persistent conflict. Youth unemployment rates in European countries always used to be higher than average unemployment rates. This has not only to be defined as an individual but also as a structural phenomenon. Since socialization via work is still highly relevant and an aspect of the future European integration, youth unemployment occurs to be a very crucial issue for sociological research. This means a research that reflects the mutual constitution or interplay of individual and collective processes as well as the drag effects of institutional and individual behavior. The paper investigates this debate and asks whether one could one speak of a “forgotten generation” or even of a “generation without future” in Europe. It exemplifies several empirical studies and develops a framework for future research.